Thermoelectric cooler (TEC) based thermal control system for space applications: Numerical study. (April 2023) - Singh, V.K.; Sisodia, S.S.; Patel, Akshat; Shah, Tirth; Das, Prasanta; Patel, R.N.; Bhavsar, R.R.
Highlights: Performance of TEC based thermal control system for optical payloads is evaluated. Fixed Set point are supplied to TEC with temperature dependent current input. Effect of different parameters on system's performance are evaluated. Performance of system at different heat loads and duty cycles is also investigated. System is investigated for cyclic steady state across multiple operating cycles. Abstract: The present study devises and numerically investigates a new thermal control system for detectors of optical payloads for spacecraft systems. The system uses thermoelectric coolers (TECs) as the active element which maintains the cold finger at the required set point such that temperature of detectors is maintained within the required range throughout its operation. The system doesn't utilize any heat pipe network, but instead, uses radiators attached to the hot-side of TEC to dissipate the heat load into the ambient space environment. System level modelling using effective properties are used to model the performance of TEC without modelling any internal intricate geometry. Temperature dependent current profiles are used as input conditions for the TECs such that the TEC consume only the required amount of external power. Effect of TEC set point and geometrical parameters of the radiator is studied and it is observed that considerable reduction in power consumption or improvement in coefficient of performance is obtained by utilizing a larger set point or a radiator with larger dimensions. The system is further investigated for different heat loads and duty cycles (upto 50% for an orbit period of 100 mins) to evaluate its efficacy under varying operating conditions. The system is also investigated for successive operating cycles and it is observed that the cyclic error between successive cycles eventually diminishes to zero thus implying that the temperature control requirements are met for successive cycles throughout the life of the system.